Effect of airway management strategies during resuscitation from out-of-hospital cardiac arrest on clinical outcome: A registry-based analysis. (July 2020) - Behrens, Niels-Henning; Fischer, Matthias; Krieger, Tobias; Monaco, Kathleen; Wnent, Jan; Seewald, Stephan; Gräsner, Jan-Thorsten; Bernhard, Michael
Abstract: Aim: An effective airway management is pivotal for treating hypoxia and to ensure reoxygenation during cardiopulmonary resuscitation (CPR). This matched-pair analysis from the German Resuscitation Registry (GRR) investigates the outcomes of various methods of airway management used on out-of-hospital cardiac arrest (OHCA) patients. Methods: 89, 220 OHCA patients were reported between 01/01/2007 and 12/31/2017. After applying exclusion and inclusion criteria, the resulting 19, 196 patient's data were analyzed. Endpoints were return of spontaneous circulation (ROSC), hospital admission, 24-h survival, hospital discharge, and discharge with cerebral performance categories 1, 2 (CPC1, 2). Three categories of airway management were defined: endotracheal tube ("ETT"), laryngeal tube ("LT_only"), and laryngeal to endotracheal tube exchange ("LTEX"). The groups were matched with respect to age, gender, aetiology or location of OHCA, witnessing or CPR by lay people, initial rhythm, and use of epinephrine and amiodarone. Results: "ETT" versus "LT_only" was associated with higher short- and long-term outcome rates and better neurological recovery (CPC_1.2: 7.7 vs. 5.8%, OR = 1.35, 95%-CI = 1.09–1.67, n = 5552). "LTEX" versus "LT_only" showed significantly higher ROSC- and 24-h survival rate (33.7 vs. 21.8%, OR = 1.82, 95%-CI = 1.51–2.2, n = 2302). "LTEX" versus "ETT" revealed significantly higher ROSC- and 24-h survival rate (34.6 vs. 30.4%, OR = 1.21, 95%-CI = 1.03–1.42, n = 2608). Conclusion: "ETT" was associated with higher survival rates and better neurological outcomes in comparison to "LT_only". The strategy of "LTEX" versus "LT_only" or "ETT" was only associated with better short-term outcomes. Our observational registry data suggests that endotracheal intubation by physician staffed EMS is the optimal airway strategy for OHCA in our system.